Mapping the Publications on an Economically Important Freshwater Crayfish, Pontastacus leptodactylus, Based on Web of Science - Aydin, Hamdi; Harlioglu, Muzaffer Mustafa; Guney, Cengiz (Inst Zoology, Bas, 2025)
We provide a comprehensive survey on the bibliometric analysis of scientific publications on Pontastacus leptodactylus published in Web of Science (WoS). We found, based on 822 WoS publications, that countries such as T & uuml;rkiye, France and Iran were among the leading contributors in this field during 1965-2023. T & uuml;rkiye led with 216 publications, followed by France with 116 and Iran with 64 publications. The majority of publications consisted of articles, while Fisheries, Marine and Freshwater Biology and Zoology were among the main focus categories of publications. Comprehensive analysis identified some of the main academic trends in the field by detailing the scientific knowledge and collaboration networks in research on P. leptodactylus. In conclusion, this bibliometric analysis not only highlights the significant contributions of T & uuml;rkiye, France and Iran to the study of P. leptodactylus, but also underscores the importance of collaboration and citation dynamics in shaping the academic landscape of the field, thereby providing valuable insights for future research directions.
Keywords: aquatic species; bibliometric analysis; citations; narrow-clawed crayfish; VOSviewer